Replication of overmolded orthopedic implants with a functionalized thin layer of biodegradable polymer - Elkaseer, Ahmed; Mueller, Tobias; Azcarate, Sabino; Philipp-Pichler, Martin; Wilfinger, Thomas; Wittner, Wolfgang; Prantl, Manfred; Sampaio, Daniel [UNESP]; Hagenmeyer, Veit; Scholz, Steffen (MDPI, 2018)
The present paper reports on the development of a biodegradable overmolded orthopedic implant: a metal bone fixing screw, which has been overmolded with a functionalized thin layer of biodegradable polymer to enhance cell adhesion during the healing process. The main challenges were to integrate precise, high-throughput and repeatable solutions to achieve a thin, defect-free structured polymer layer and to ensure a high and consistent implant quality. The work carried out entailed determining proper materials (Purasorb PDLG 5010) for the biodegradable overmolding layer and its economical substitute (NaKu PLA 100HF) to be used during initial tool and process development, designing the surface structure of the overmolded polymer layer, development of injection molding tools, as well as feeding and handling procedures. The injection overmolding process of Purasorb PDLG 5010 polymer was controlled, and the process parameters were optimized. In particular, the dominant process parameters for the overmolding, namely injection pressure, barrel temperature and mold temperature, were experimentally examined using a circumscribed three-factor central composite design and two quality marks; overmolding roughness and mass of polymer. The analysis of the experimental results shows that the mass of the overmolding is not feasible for use as the quality mark. However, the optimal parameters for the overmolding of a metallic implant screw with a thin, micro-structured polymer layer with a predefined roughness of the surface texture have been identified successfully.
Keywords: Biodegradable polymer; Functionalized surface; Micro injection molding; Orthopedic implants; Process optimization